Analisi Peran Media Pembelajaran Interaktif Berbasis Kahoot Terhadap Motivasi Belajar Siswa Dalam Pembelajaran Daring - Karin Widya Ayuningtyas; Nadhirotuz Zulfah (Proceedings Series on Social Sciences & Humanities, 2021)
The Covid-19 pandemic that has spread throughout the country has made the government decide teaching and learning activities to be carried out boldly (online). Learning makes students bored and eventually lazy to learn. Researchers are trying to create new breakthroughs to increase student learning motivation to increase, namely by utilizing interactive learning media based on kahoot in brave learning. This study uses a literature review method where the data obtained from research comes from articles or journals that are relevant to the topic, or other people's research results are then analyzed again to draw a conclusion. The results of this research kahoot interactive media can be used in bold learning because of its easy use and includes a link or website so that it can be accessed by students. This interactive media also makes students not easily bored in the learning process. Learning that increases in fun can make students' learning motivation, this is because students do not feel bored easily when learning takes place, so students feel motivated and feel comfortable when learning using Kahoot media.